不同产地山桐子品质分析及综合评价 Quality analysis and comprehensive evaluation of Idesia polycarpa - 邹康，常云鹤，宋明发，刘晓燕，何劲，马立志 ZOU Kang, CHANG Yunhe, SONG Mingfa, LIU Xiaoyan, HE Jin, MA Lizhi (Zhongguo youzhi)
旨在探究不同产地山桐子果实成分及油脂品质的差异性，对7个不同产地山桐子果实的基本成分及其油脂的品质指标进行测定，通过层次聚类分析对山桐子品质指标进行差异性分析，通过主成分分析对山桐子特征品质指标进行综合评价。结果表明：不同产地山桐子果实的含油率以及蛋白质、灰分、粗纤维、总糖、总酚、总黄酮含量存在一定差异；不同产地山桐子油的脂肪酸组成无显著差异，脂肪酸含量存在一定差异，但均为亚油酸含量最高（69.92%~74.96%），陕西汉中和云南威信的不饱和脂肪酸含量较高；陕西汉中山桐子油的角鲨烯、维生素E含量最高，分别为170.95、266.12 mg/100 g；四川泸州山桐子油的β-谷甾醇含量(472.42 mg/100 g)最高；四川绵阳山桐子油的总酚含量(28.45 mg/100 g)最高；贵州榕江山桐子油的磷脂含量(4.29 mg/100 g)最高；聚类分析结果显示，陕西汉中、四川泸州、云南威信、贵州仁怀山桐子为一类，贵州贵阳、贵州榕江、四川绵阳山桐子为一类；主成分分析结果显示，陕西汉中山桐子综合得分最高，云南威信的次之。综上，产地是影响山桐子品质的因素之一。 In order to explore the difference of fruit composition and oil quality of Idesia polycarpa Maxim from different geographic regions, the quality indexes of fruit and oil of Idesia polycarpa Maxim from 7 different geographic regions were determined, the differential analysis of quality indexes of Idesia polycarpa Maxim were analyzed by hierarchical cluster analysis, and the quality of Idesia polycarpa Maxim from different geographic regions was evaluated comprehensively by principal component analysis. The results showed that there were certain degree of differences in contents of oil, protein, ash, crude fiber, total sugar, total phenol and total flavone in fruit of Idesia polycarpa Maxim from different geographic regions. There was no significant difference in fatty acid composition of Idesia polycarpa Maxim oil from different geographic regions, with some difference in fatty acid content, but the content of linoleic acid was the highest (69.92%-74.96%), and the content of unsaturated fatty acid was higher in Hanzhong, Shaanxi Province and Weixin, Yunnan Province. The contents of squalene and vitamin E in Idesia polycarpa Maxim oil from Hanzhong, Shaanxi Province were the highest (170.95, 266.12 mg/100 g, respectively), and the content of β-sitosterol in Idesia polycarpa Maxim oil from Luzhou,Sichuan Province was the highest (472.42 mg/100 g). Idesia polycarpa Maxim oil from Mianyang, Sichuan Province had the highest total phenol content (28.45 mg/100 g). The highest phospholipid content (4.29 mg/100 g) was found in Idesia polycarpa Maxim oil from Rongjiang, Guizhou Province. The cluster analysis results showed that the Idesia polycarpa Maxim from Hanzhong, Shaanxi Province, Luzhou, Sichuan Province, Weixin, Yunnan Province and Renhuai, Guizhou Province were in one category, the Idesia polycarpa Maxim from Guiyang, Guizhou Province, Rongjiang, Guizhou Province and Mianyang, Sichuan Province were in another category. The results of principal component analysis showed that the Idesia polycarpa Maxim in Hanzhong, Shaanxi Province had the highest comprehensive evaluation score, followed by Weixin, Yunnan Province. To sum up, the geographic region is one of the factors affecting the quality of Idesia polycarpa Maxim.